Electrochemical properties of nickel phthalocyanine: The effect of thin film morphology tuned by deposition techniques - Furini, Leonardo N. [UNESP]; Martin, Cibely S. [UNESP]; Camacho, Sabrina A. [UNESP]; Rubira, Rafael J.G. [UNESP]; Fernandes, José Diego [UNESP]; Silva, Edilene A. [UNESP]; Gomes, Tiago C. [UNESP]; Stunges, Gabriele M. [UNESP]; Constantino, Carlos J.L. [UNESP]; Alessio, Priscila [UNESP] (Elsevier, 2020)
The electrical and optical properties of thin films can be modulated by its supramolecular arrangement being this latter closely related to the fabrication method. Here, we are exploiting the impact of deposition techniques of nickel phthalocyanine (NiPc) and tetrasulfonated nickel phthalocyanine (NiTsPc) thin films on their supramolecular arrangement. Deposition techniques as Langmuir-Schaffer (LS), Langmuir-Blodgett (LB), physical vapor deposition (PVD), dipping- and spray-Layer-by-Layer (LbL) were applied for fabrication of the thin films. Linear growth was observed for all films indicating control of the amount of NiPc or NiTsPc deposited in each technique at nm scale. Fourier-transform infrared absorption spectroscopy (FTIR) and micro-Raman scattering confirmed the chemical stability of NiPc and NiTsPc concerning the deposition technique (water or heat). Besides, FTIR and X-ray diffraction data suggested that all thin films present isotropy in terms of molecular organization, with a predominance of the crystalline α-phase in the case of PVD, LB, and LS films. Atomic force microscopy images revealed irregularities at the surface for all thin film with the roughness/thickness ratio being 4.5% for PVD, 9% for both LB and LS films, and 18 and 35% for spray- and dipping-LbL films, respectively. The electrochemical behavior in both inert electrolyte and dopamine (DA) solution was directly dependent on the film morphology (molecular aggregates and surface roughness). The increase of the roughness in relation to thickness promoted films better electrochemical responses to DA oxidation. The dipping-LbL films showed the smaller potential of DA oxidation (0.114 V), even compared to the bare substrate (0.133 V). The deposition technique showed to be an suitable tool to tune the supramolecular arrangement of phthalocyanine forming thin films, which improve and/or change the electrochemical properties of the device.
Keywords: Nickel phthalocyanine; Supramolecular arrangement; Thin films